Acidogenesis, solventogenesis, metabolic stress response and life cycle changes in Clostridium beijerinckii NRRL B-598 at the transcriptomic level - Patakova, Petra; Branska, Barbora; Sedlar, Karel; Vasylkivska, Maryna; Jureckova, Katerina; Kolek, Jan; Koscova, Pavlina; Provaznik, Ivo (Scientific reports, 2019)
Clostridium beijerinckii NRRL B-598 is a sporulating, butanol and hydrogen producing strain that utilizes carbohydrates by the acetone-butanol-ethanol (ABE) fermentative pathway. The pathway consists of two metabolic phases, acidogenesis and solventogenesis, from which the latter one can be coupled with sporulation. Thorough transcriptomic profiling during a complete life cycle and both metabolic phases completed with flow cytometry, microscopy and a metabolites analysis helped to find out key genes involved in particular cellular events. The description of genes/operons that are closely involved in metabolism or the cell cycle is a necessary condition for metabolic engineering of the strain and will be valuable for all C. beijerinckii strains and other Clostridial species. The study focused on glucose transport and catabolism, hydrogen formation, metabolic stress response, binary fission, motility/chemotaxis and sporulation, which resulted in the composition of the unique image reflecting clostridial population changes. Surprisingly, the main change in expression of individual genes was coupled with the sporulation start and not with the transition from acidogenic to solventogenic metabolism. As expected, solvents formation started at pH decrease and the accumulation of butyric and acetic acids in the cultivation medium.
Keywords: transkriptom; Glucose; vodík; Hydrogen; Bacterial Proteins; Solvents; Clostridium beijerinckii; rozpouštědla; mastné kyseliny; kyseliny; Transcriptome; spory bakteriální; glukosa; Heat-Shock Proteins; Fatty Acids; regulace genové exprese u bakterií; fermentace; Stress, Physiological; Acids; Spores, Bacterial; bakteriální proteiny; Fermentation; fyziologický stres; Gene Expression Regulation, Bacterial; proteiny teplotního šoku